Linguistic evaluation of the albanian alternative to foreign words in standard albanian - Jorgaqi, Kristina (Zeitschrift für Balkanologie, 2005)
The paper represents the first effort to analyse the planned activity that has been under¬taken during the 1980’s to “purify” the Albanian language from some hundreds of “unnecessary loans” and enrich it with “native” words. Once the author places the issue in a historical cultural background, she dwells on minutely identifying and evaluating the linguistic features that characterize the “products” of this activity to reveal, among other things, the motives that inspired her and gave rise to it.